REPLACEMENT OF INFORMATION TECHNOLOGIES IN THE ORGANIZATION OF EXTRA-CURRICULAR ACTIVITIES IN GENERAL SECONDARY SCHOOLS (IN THE EXAMPLE OF TEACHING NATURAL SCIENCES) (Scientific journal of the Fergana State University, 2023)
In this article, the role of extracurricular activities in improving the educational experience of students in general secondary schools, their importance, and the advantages of using information technologies are shown.